5.9 FEATURES OF THE DEVELOPMENT OF COMMUNICATION AND TRANSPORT IN UZBEKISTAN - 1. Salimov Bakhriddin Lutfullaevich. Professor at Tashkent State Transport University. 2. Abdukarimov Jumanazar Abdufatto o‘g‘li. Student at Tashkent State Transport University. (Innovative technologies in construction Scientific Journal, 2024)
Annotation The article analyzes the fact that in recent years there have been radical reforms in both domestic and foreign policy of our state, the reforms that have begun are beginning to show their positive results in short periods, in particular, universal changes are taking place in the communication and transport system.